The Quranic Memorization Learning Process Based on STIFIn Intelligence Test Results - Muhammad Yusuf; Rizka Harfiani; Hasrian Rudi Setiawan (Dinasti International Journal of Education Management And Social Science, 2024)
The aim of this study is to evaluate the Quran memorization learning process using the results of the STIFIn intelligence test as a reference. This is done by analyzing the planning, implementation, and assessment of learning. The study adopts a qualitative approach with a descriptive research type. The research location was chosen at SD Abi And Ummi, Medan, based on initial observations that showed the application of the STIFIn method in Quran memorization learning. The subjects of the research consisted of school administrators, teachers, and students, totaling 3 administrators, 14 teachers, and 57 students. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the stages of collection, reduction, presentation, and conclusion drawing. The results of the study show that Quran memorization teachers plan their lessons by utilizing the results of the STIFIn intelligence test. They adjust their teaching methods to the students' learning styles, as seen in children with Feeling intelligence who are more responsive to audio-based learning. School documentation also confirms the existence of systematic planning, including the use of the STIFIn intelligence test as an initial step to understand student characteristics. With active involvement from school management, these programs have the potential to be further improved so that Quran memorization lesson planning based on the results of the STIFIn intelligence test can be more effective and efficient in the future. SD Abi And Ummi demonstrates a strong commitment to enhancing Quran learning by understanding student characteristics through the STIFIn test. Structured support from administrators, teachers, and students aims to optimize the quality of learning based on the results of the STIFIn intelligence test. This assessment is crucial in ensuring that each student receives support according to their needs, thereby improving learning outcomes in Quran memorization.